PENERAPAN MODEL COMPLETE SENTENCE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 42 PIDIE - Nia Wardhani; Putri Ramadhani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The aim of the study was to find out if Complete Sentence Model could improve learning outcomes of 4th grade students’ of MIN 42 Pidie. The research was carried out in two cycles. The procedures consisted of planning, acting, observing and reflecting. The subject of the research was the 4th grade students; they were 19 students totally which are 7 boys and 12 girls. The result showed the average and classical achievement: cycle I are 68.1 and 42%; cycle II was 89.2 and 100%. Thus, Complete Sentence Model can improve the students’ learning outcomes.